Neurological Soft Signs (NSS) in Census-Based, Decade-Adjusted Healthy Adults, 20 to >70 Years of Age - Bachmann, Silke; Beck, Michaela; Tsai, Dai-Hua; Haupt, Friederike (Frontiers in Psychiatry, 2021)
Neurological Soft Signs (NSS) represent minor neurological features and have been widely studied in psychiatric disease. The assessment is easily performed. Quantity and quality may provide useful information concerning the disease course. Mostly, NSS scores differ significantly between patients and controls. However, literature does not give reference values. We recruited 120 healthy women and men to build a representative, cross-sectional, census-based sample of healthy individuals, aged 20 to >70 years, subdivided in 10-year-blocks for a close approach to the human lifeline. Testing for NSS and neurocognitive functioning was performed following the exclusion of mental and severe physical illness. NSS scores increased significantly between ages 50+ and 60+ which was primarily accountable to motor signs. Gender and cognitive functioning were not related to changes of scores. Although the number of individuals is small, study results may lay a foundation for further validation of NSS in healthy individuals.